Plasma fibrinogen, d-dimer, and fibrin degradation product as biomarkers of rheumatoid arthritis - Li Xue (Nature Portfolio, 2021)
Abstract This study aimed to assess the association of coagulation-related indicators such as plasma fibrinogen (FIB), d-dimer, and fibrin degradation product (FDP) in rheumatoid arthritis (RA) with the disease activity. Data from 105 RA patients and 102 age- and gender-matched healthy controls were collected in the retrospective study. Disease activity score in 28 joints based on C-reactive protein (DAS28-CRP) was used to divide RA patients into low activity group (DAS28-CRP ≤ 2.7) and active group (DAS28-CRP > 2.7). Receiver operating characteristic (ROC) curve was applied to determine area under the curve (AUC). The association between plasma FIB, d-dimer, and FDP and DAS28-CRP was evaluated by spearman correlation. Logistical regression analysis was used to identify the independent variables associated with RA disease activity. RA patients showed higher levels of plasma FIB, d-dimer, and FDP than the controls (P < 0.01). Plasma FIB, d-dimer, and FDP were also increased in active groups of RA patients than those in inactive groups (P < 0.001). ROC curve analyses revealed that the AUC of d-dimer was higher than erythrocyte sedimentation rate (ESR) and rheumatoid factor (RF), and that of FDP was higher than RF in RA patients. In addition, the optimal cut-off value of plasma FIB, d-dimer, and FDP for RA diagnosis was 286 mg/dL, 470 μg/L, and 1.45 mg/L, respectively. Spearman analysis showed that plasma FIB, d-dimer, and FDP were positively related with DAS28-CRP (P < 0.001) in RA patients. Logistical regression analysis showed that d-dimer (odds ratio 2.862, 95% confidence interval 1.851–5.426, P < 0.001) was an independent variable associated with RA disease activity. FIB, d-dimer, and FDP were increased in RA patients and positively correlated with the disease activity of RA. d-dimer may act as a novel inflammatory indice for indicating disease activity in RA patients.